Microbial ecology and fermentation of Coffea canephora - Bernardes, Patrícia Campos; Coelho, Jussara Moreira; Martins, Pâmela Mynsen Machado; Schwan, Rosane Freitas (Frontiers in Food Science and Technology, 2024)
Recent investigations into the microbiota and fermentation of Coffea canephora fruits and beans have yielded limited advancements globally, highlighting a developing field of study. Consequently, this review seeks to consolidate existing literature through an analysis focusing on the microbiota and fermentation processes inherent in the postharvest processing of Canephora coffee. To this end, a comprehensive examination of the principal microorganisms inherent to this species, the application of starter cultures in fermentation, and the repercussions of fermentation on the chemical and sensory attributes of the beverage will be expounded. These investigations underscore the influence exerted by the fermentation process and the introduction of microorganism inoculation on Canephora coffees’ chemical composition and sensory characteristics. Fermentation emerges as a mechanism facilitating the modification of coffee flavor and aroma, thereby presenting avenues for innovative enhancements in producing distinct Canephora coffee beverages. Research to assess the microbiota of Canephora coffees from various origins has the potential to advance our understanding of the microbial ecology specific to this species. Such studies will play a crucial role in identifying pertinent starter cultures that could be used to produce high-quality coffees.